DETECTION OF SPATIAL, TEMPORAL, AND SPECTRAL SURFACE CHANGES IN THE NY-ÅLESUND AREA 79° N, SVALBARD, USING A LOW COST MULTISPECTRAL CAMERA IN COMBINATION WITH SPECTRORADIOMETER MEASUREMENTS - Hinkler J.; Hansen B.U.; Ørbæk J.B. (My University, 2003)
Changes in surface reflection at the arctic tundra at Ny-Ålesund, Svalbard (79° N) were monitored during the melting season 2002 using a low cost multispectral digital camera with spectral channels similar to channels 2, 3, and 4 of the Landsat Thematic Mapper satellite sensor. The camera was placed 474 m above sea level at the Zeppelin Mountain Research Station and was programmed to take an image automatically every day at solar noon. To achieve areal consistency in the images (which is necessary for mapping purposes) the images were geometrically rectified into multispectral digital orthophotos. In contrast to satellite images with high spatial resolution the orthophotos provide data with high spatial and high temporal resolution at low cost. The study area covers approximately 2 km2 and when free of snow, it mainly consists of typical high arctic tundra with patchy vegetation and bare-soil in between. The spectral information in the images was used to divide the rectified images into maps representing different surface classes (including three subclasses of snow). By combining classified image data and ground measurements of spectral surface reflectance, a methodology to produce daily maps of surface albedo was developed. The method takes into account the effect of decreasing snow-albedo with ageing snow pack, and the very rapid decrease of albedo when the snow pack is shallow (